The role of pomegranate seed oil on kidney and lung tissues in the treatment of sepsis: animal pre-clinical research - Arslan, Mustafa; Küçük, Ayşegül; Bozok, Ümmü Gülşen; Ergörün, Aydan İremnur; Sezen, Şaban Cem; Yavuz, Aydın; Kavutçu, Mustafa (The Journal of Infection in Developing Countries, 2023)
Objectives: Sepsis is a common disease with a high mortality. Decreasing the speed is possible with early and intensive therapy. However, most medicines have been tested, but none has proven effective. Therefore, the study aimed to discover the protective and therapeutic effects of pomegranate seed oil (PSO). Methods: The cecal ligation puncture (CLP) method was used to induce sepsis. The experimental procedure was started with the animals divided haphazardly into four groups: control (C), sepsis (CLP), CLP + low dose PSO (CLP + LD), and CLP + high dose PSO (CLP + HD). First, the cecum was filled with feces. The full cecum was tied under the ileocecal valve for ligation and punctured. At 1 hour after CLP, 0.32 mg/kg and 0.64 mg/kg of PSO were administered. 24 hours after, lung and kidney specimens were collected. Results: Neutrophil infiltration/aggregation and alveolar wall thickness decreased in lung with PSO groups compared with the CLP. The findings for overall lung injury were similar. In renal, all parameters were increased in the CLP compared with C, except for vascular vacuolization and hypertrophy. According to the CLP, all parameters were significantly lower in CLP + HD. Furthermore, glomerular vacuolization, degeneration, and necrosis of tubular cell, dilatation of bowman space, and tubular hyaline cylinders reduced CLP + LD versus CLP. Thiobarbituric acid-reactive substances decreased in lung, with the PSO groups. In addition, superoxide dismutase increased in PSO groups versus CLP. Conclusions: We conclude that the high-dose PSO is especially effective in treating sepsis.